Influenza B/Victoria outbreak in a remote mountainous village: Oddar Meanchey Province, Cambodia, July–August 2023 - Pong, Khemrin; Ung, Sophanith; Yi, Sengdoeurn; Long, Sovannara; Chhoung, Siphai; Nhim, Kimthy; Long, Hayputhik (Western Pacific Surveillance and Response, 2025)
Objective: A response team was deployed to rural Oddar Meanchey Province, Cambodia, in mid-August 2023, immediately after a cluster of patients with acute febrile illness was reported. The team aimed to identify the cause of the outbreak and analyse the epidemiological characteristics and associated risk factors. Methods: This retrospective cohort study involved all residents of Prasat Rumdoul Village. A case was defined as a resident with a fever >=38°C or a history of fever with symptoms such as cough, sore throat or coryza occurring from 18 July to 18 August. Demographic data, information about infection prevention practices and clinical information were collected using structured questionnaires and analysed using binomial regression. Laboratory samples were collected, and confirmatory laboratory tests and environmental investigations were also conducted. Results: Among the 126 villagers, 95 cases were identified (attack rate: 75.3%); 52 (54.7%) were female, and the median age was 29 years. Prolonged close contact with individuals who had influenza-like illness significantly increased the risk of infection (adjusted risk ratio [ARR]: 2.19, P = 0.002). Protective factors included mask-wearing (ARR: 0.26, P = 0.003) and regular handwashing (ARR: 0.85, P = 0.012). No villagers had been vaccinated against influenza within the past 1 year. Laboratory tests confirmed influenza type B/Victoria as the causative agent. Poor adherence to preventive measures and crowded living conditions contributed to the outbreak. Discussion: The outbreak was caused by influenza type B/Victoria, the same strain circulating in nearby Thailand. Public health interventions to improve vaccine accessibility and hygiene-promotion activities would be useful for preventing future outbreaks.